Genotype and agronomic management interaction to enhance wheat yield and water use efficiency in the Mediterranean rainfed environment of Morocco: I. Field data analysis - Devkota Wasti, Mina Kumari; Devkota, Krishna; Karrou, Mohammed; Nangia, Vinay (Elsevier, 2023)
Durum wheat (Triticum turgidum subsp. durum), considered better drought tolerant, is the most cultivated wheat in Morocco and in the Middle East and North Africa (MENA) region. The region, including Morocco, predominantly has rainfed production systems, declining water supply, and increasing trends and effects of rainfall variability and climate extremes leading to poor crop yield and yield stability. The objectives of this study were to understand major factors determining wheat yield and water use efficiency (WUE); assess the interaction of genotype × environment × management on crop yield and field- and crop-water use efficiencies; and determine the water-limited yield gaps of genotypes under different agronomic management practices in the Mediterranean climate of Morocco. Four years (2015/16–2018/19) of on-station experiments investigating genotype (ten ge notypes including seven advanced line and three commercial varieties), seeding time (17 November vs. 29 December), and water management (rainfed vs. supplementary irrigation), was conducted at Merchouch research station, Morocco. The results showed that durum wheat yield mostly varied due to year (rainfall) by 43%, followed by water management × year (23%), year × seeding time (15%), and genotype (7%), with the highest yield (7.15 t ha− 1 ) observed in 2018 (wet year) and the lowest in 2019 (dry year). Across years, not only the rainfall amount but also its distribution during the crop growing season caused yield variability. In low rainfall years, supplementary irrigation (28–166 mm) increased yield by 2.12–3.27 t ha− 1 compared to rain fed conditions. The significant (p < 0.01) year × seeding time × genotype effect on grain yield and WUEs in dicates that the response of genotype and seeding time varied with rainfall amount and distribution as the water limited yield gap in rainfed conditions appeared to be more than 2 t ha− 1 . In both supplementary irrigated and rainfed systems, the machine learning model showed the effect of different climatic (rainfall and temperature) and management (seeding time, genotype, and irrigation) factors determining yield, yield attributes, and WUEs. The total rainfall remained the most important factor explaining variation in rainfed wheat yield followed by the temperature at flowering, mid- and early-season rainfall, and genotype in order of importance. Similarly, sea sonal rainfall was the most important factor explaining variation in grain yield followed by early-season rainfall, days to flowering, temperature at flowering, irrigation amount, seeding time, and genotype in supplementary irrigated durum wheat. Our study clearly shows that yield is highly related to rainfall in rainfed drylands, and the selection of high WUE variety and crop management practices are the key to improving the resilience and sustainability of durum wheat in Morocco and similar production environments in the MENA region.